Pengaruh Green Marketing dan CSR Terhadap Purchase Decision dengan Brand Image sebagai Intervening - Putri Najla Afifah Adianto (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This research aims to analyze the influence of green marketing and corporate social responsibility on purchase decisions with brand image as an intervening variable. This research was conducted by conducting a survey of Generation Z consumers of Sosro bottled tea in Yogyakarta. The sampling technique in this research is purposive sampling. This research uses a quantitative approach and the data source is obtained from a questionnaire of 100 respondents. The analysis tool used is Partial Least Square (PLS) with SmartPLS 4.1.0.0 Software. This research shows that green marketing and corporate social responsibility have a positive and significant effect on brand image. Green marketing has a positive and significant effect on purchase decisions. Corporate social responsibility has a positive but not significant effect on purchase decisions. Green marketing and corporate social responsibility have a positive and significant effect on purchase decisions through brand image.